1997
DOI: 10.1161/01.cir.96.3.984
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning

Abstract: Three-cycle IP provided more effective protection against myocardial necrosis than one-cycle IP and was less susceptible to blockade by inhibitors of PKC or an agent that increases cAMP levels. However, single-cycle IP was only partially blocked by either inhibition of PKC or stimulation of cAMP production. Neither activation of the PKC pathway nor reduced formation of cAMP alone fully accounted for the necrosis protection by IP even when induced with only a single cycle of transient ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…A previous study in rabbits had suggested that IP is a dose-dependent phenomenon (17). We have therefore tried to increase the protection of IP by increasing the number of preconditioning ischemia-reperfusion cycles from one to four with the aim to possibly attenuate this greater protection with TNF-␣ antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in rabbits had suggested that IP is a dose-dependent phenomenon (17). We have therefore tried to increase the protection of IP by increasing the number of preconditioning ischemia-reperfusion cycles from one to four with the aim to possibly attenuate this greater protection with TNF-␣ antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Because hypoxia-reoxygenation transition is also part of the protocol of ischemic preconditioning, it may be supposed that the described mechanism of protection is contained within the complex protective mechanism of ischemic preconditioning. It is possibly responsible for the finding in some biological models that ischemic preconditioning can provide myocardial protection independent of PKC activation (20,21,23,27).…”
Section: Discussionmentioning
confidence: 99%
“…cellular calcium; heart function; ischemia; reperfusion SEVERAL STUDIES (18,25,32) have demonstrated that protection of the myocardium against ischemia-reperfusion injury caused by a brief preceding ischemia (ischemic preconditioning) is due to the release and accumulation of endogenous mediators, such as adenosine or noradrenaline, during ischemic preconditioning and a subsequent activation of protein kinase C (PKC). There are, however, data (20,23,27) indicating that protection by ischemic preconditioning can also be achieved independent of PKC activation. The mechanism of this PKC-independent protection could not be explained.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 for overview of protocols). The duration of this stabilization period has been shown to be sufficiently long to exclude an effect of the surgical procedures on the development of infarct size (28).…”
Section: Experimental Protocols/designmentioning
confidence: 99%